2017
DOI: 10.14746/ssllt.2017.7.4.2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of contemplative practices on foreign language anxiety and learning

Abstract: This study looked at the impact of the integration of contemplative practices on foreign language anxiety, positive and negative affect, self-efficacy, classroom climate, and language learning in students enrolled in an advanced intermediate Spanish language course in the USA. Data included pre-and post-test surveys, exam scores to measure learning outcomes, student interviews, and course evaluations. In the contemplative group, students engaged in brief 10-minute contemplative practices once a week, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Our review further found learner-internal features of FLAR interventions. Five studies used performance such as drama ( Sağlamel and Kayaoğlu, 2013 ; Galante, 2018 ; Uştuk and Aydın, 2018 ; Kwiecień-Niedziela et al, 2020 ) or digital storytelling ( Liu et al, 2018 ), five involved strategies ( Alrabai, 2015 ; Mostafavi and Vahdany, 2016 ; He, 2017 ; Tsiriotakis et al, 2017 ; Bielak, 2018 ), four interventions used counseling and training ( Abood and Abu-Melhim, 2015 ; Kralova et al, 2017 , 2018 ; Toyama and Yamazaki, 2019 ), and four used mood boosters such as meditation ( Scida and Jones, 2017 ), music ( Shimbo, 2008 ), gaming ( Wei et al, 2018 ), and web-based L2 exercises ( Bashori et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review further found learner-internal features of FLAR interventions. Five studies used performance such as drama ( Sağlamel and Kayaoğlu, 2013 ; Galante, 2018 ; Uştuk and Aydın, 2018 ; Kwiecień-Niedziela et al, 2020 ) or digital storytelling ( Liu et al, 2018 ), five involved strategies ( Alrabai, 2015 ; Mostafavi and Vahdany, 2016 ; He, 2017 ; Tsiriotakis et al, 2017 ; Bielak, 2018 ), four interventions used counseling and training ( Abood and Abu-Melhim, 2015 ; Kralova et al, 2017 , 2018 ; Toyama and Yamazaki, 2019 ), and four used mood boosters such as meditation ( Scida and Jones, 2017 ), music ( Shimbo, 2008 ), gaming ( Wei et al, 2018 ), and web-based L2 exercises ( Bashori et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 2 , contemplative practices and relaxation were placed between self-management and mood boosters since these methods work on thoughts and feelings. Results concerning contemplative practices ( Scida and Jones, 2017 ) and relaxation ( Shimbo, 2008 ) remain unclear. Psychologists have demonstrated the effects of contemplative practices such as mindfulness and meditation on physical and psychological health and well-being (see a review by Dorjee, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…These changes might be credited to ameliorated living standards and an overall decline in stress levels. Although based on contemplative practices that are not pranayama centered, Scida and Jones’s (2017) bears a direct resemblance to the qualitative findings of the study as the researchers too found that language learners regarded the practices as quite useful and felt calmer and relaxed during language classes. It was also previously proved that yoga and pranayama enhance the quality of life and sleeping in general ( Önder, 2019 ).…”
Section: Discussionmentioning
confidence: 55%
“…Another strand of research examined instructional design addressing the cognitive and emotional dispositions of learners: While Oghyanous (2017) for brain-based teaching and Balci (2017) for learning style oriented teaching showed impacts, Scida and Jones (2017) did not reveal any statistically significant differences between pre-and post-test or experimental and control group in self-efficacy beliefs related to stress management of university students receiving contemplative practices.…”
Section: Self-efficacymentioning
confidence: 99%